EFEKTIVITAS PENGGUNAAN AUGMENTED REALITY (AR) DALAM MENINGKATKAN HASIL BELAJAR SISWA SD PADA MATA PELAJARAN IPA: LITERATURE REVIEW - Widya Mufidatul ‘Ula; Eka Duwi Ardianti; Nadya Ayu Lifiani; Mu’minatut Towafiah; Audy Putri Cahyani; Nurul Mahruzah Yulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning is an activity carried out by each individual with the aim of causing a change in behavior from interaction with the environment and learning resources. Digital technology has opened up new opportunities for educational transformation as an innovation and improvement in the quality of learning, especially in improving the effectiveness of learning at the Elementary School level, one of which is Augmented Reality (AR) with a learning concept that combines the real world with virtual elements in real-time. This study adopts a literature review method by collecting and analyzing